Climate change and dam development: Effects on wetland connectivity and ecological habitat in tropical wetlands. Issue 6 (9th June 2020) - Nielsen, Daryl L.; Merrin, Linda E.; Pollino, Carmel A.; Karim, Fazlul; Stratford, Danial; O'Sullivan, Jackie
Abstract: Wetlands are one of the most threatened ecosystems on earth. Globally, there is growing demand to develop infrastructure to harvest water resources to support agriculture, threatening the ecological integrity of associated wetland ecosystems. We investigated the potential ecological impacts on floodplain wetland connectivity in northern Australia in response to changes in flow regime due to dam construction and climate change. Results for this study indicate that a drier climate and/or dam construction in catchments have the potential to reduce the effective size of the floodplain and reduce wetland connectivity. A drier climate will reduce rainfall and subsequent catchment run‐off, resulting in a decrease in the magnitude of riverine flows. In contrast, dams in the upper catchment will reduce the magnitude of flows downstream. The reduction in flows under both dam development and a drier climate will result in reduced extent and duration of floodplain inundation and decreased wetland connectivity. As a result, we anticipate that this loss of connectivity will reduce the capacity for nutrients, carbon and primary production to be flushed into the river channel, as well as reduce the ability for biota such as fish and turtles to move between in‐channel and off‐channel habitats.